Temperature Induced Protein Unfolding and Folding of RNase a Studied by Time-Resolved Infrared Spectroscopy. Issue 1 (1999) - Georg, H.; Wharton, C. W.; Siebert, F.
Abstract : When a protein finds its native three-dimensional structure from the unstructured amino-acid chain various processes spanning a large time range are relevant. To understand the mechanism of protein folding one needs to cover the entire folding/ refolding (U↔N) reaction on a structural level. In the case of RNase A, the main structural changes occur in the ms time range, that can be monitored with rapid-scan- FTIR spectroscopy combined with rapid mixing techniques. To induce unfolding we inject aqueous protein solution into a hot IR cuvette and record the time course of the spectral changes. A lag phase is found when the unfolding conditions are relatively weak, suggesting an unfolding intermediate.